Finite element analysis of anisotropic optical waveguide with arbitrary index profile - Franco, Marcos A. R.; Passaro, Angelo; Cardoso, José R.; Machado, José M. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
This work presents the application of a scalar finite element formulation for Ex (TE-like) modes in anisotropic planar and channel waveguides with diagonal permittivity tensor, diffused in both transversal directions. This extended formulation considers explicitly both the variations of the refractive index and their spatial derivates inside of each finite element. Dispersion curves for Ex modes in planar and channel waveguides are shown, and the results compared with solutions obtained by other formulations.
Keywords: Anisotropic media; Finite element methods; Nonhomogeneoulsy loaded waveguides; Optical strip waveguides; Anisotropy; Computer simulation; Electromagnetic dispersion; Finite element method; Permittivity; Refractive index; Tensors; Channel waveguides; Diffused optical waveguides; Nonhomogeneously loaded waveguides; Optical waveguides